Five Seasons of Excavations (1997-2001) in Field I at Tell Beydar (Syria) - Lucio Milano; Elena Rova (Asia Anteriore Antica)
Since 1997 the Ca’ Foscari University of Venice has been taking part, as one of the official partners, in the Syro-European archaeological expedition at Tell Beydar (Northeastern Syria). A new excavation area, Field I, was opened by the Italian team on the north-eastern slope of the 3rd millennium Upper City, just inside the Inner-City Wall. After five seasons of excavation, the presence of one of the city gates has been confirmed, and the topographical layout of the area is sufficiently clear. The opening in the fortification wall was protected by two huge, massive brick structures projecting on its internal side. Through this passage, a narrow street led from the Outer City toward the mound’s central plateau. This street was flanked on both sides by large complex buildings, possibly official in character, and by small open spaces occupied by graves and dumping areas.